Essentials of soil mechanics and foundations basic geotechnics - McCarthy, David F. (Pearson, 2014)
17 Chapters, including topics on: Soil Types and Composition,Water movement, Subsurface Stresses, Soil Settlement, Earthquakes, Foundations, Site improvements and Lateral Stability.